Creative Leadership Behavior of the Madrasah Tsanawiyah Negeri’s Principals in North Sulawesi - Aswin Kiay Demak; Joulanda A. M. Rawis; Achmad Paturusi; Jeffry S. J. Lengkong (Journal of the Community Development in Asia (JCDA), 2022)
ABSTRACTThe purpose of this research is to analyze the principal’s leadership behavior and its determinant factor in 3 Madrasah Tsanawiyah (MTs) in North Sulawesi. The researchers use a qualitative and multi-site approach. The data were collected through observation, interview, and documentation studies. Meanwhile, the analysis data was adapted from the interaction model. The result shows that the principal is facilitating teachers’ creativity through internal and external factors. Also creates a realization of a creative vision of teachers through direct and indirect communication. The study also shows that some determinant characteristics have a similarity and dissimilarities function as a support factor and deterrent factor to the creative leadership behavior of MTs principals. For future research, the researchers can use quantitative data on how creative leadership variables interact with other variables.Keywords: Creative, Leadership, Principals.